Framing Leadership during Campaign Period: An Appraisal System Analysis of Op-eds during the 2022 Philippine Elections - Mangana, Mellianne (ABAC ODI JOURNAL Vision. Action. Outcome, 2025)
This study examines the framing of leadership qualities among the top two presidential candidates using Martin and White’s (2005) and Martin and Rose’s (2007) Appraisal System in the context of the 2022 Philippine elections. The study involved the collection of 78 op-eds gathered through purposive sampling based on the inclusion-exclusion criteria, which was then followed by the application of Fairclough’s (2010, 2015) three steps of critical discourse analysis: textual, processing, and social. The findings indicate that by employing emotional language, assessing leadership qualities and appreciation, and utilizing graduation devices, op-eds can sway public opinion and electoral results. Diverse sources and voices can facilitate a comprehensive and balanced discussion, enabling readers to develop their assessment of the candidates. The media’s important function in political candidate evaluation should include emotionally balanced reporting, credible assessments, nuanced analyses, and inclusion of a range of voices to limit diminishing trust in the media and reduce polarization. This paper demonstrates that the Appraisal System Framework can be an instrument for leadership evaluation, language assessment, and critical media consumption. Future studies should investigate the interaction of social media and traditional media influence in their evolving forms and platforms to shape voter opinions.